Designing Vasicine‐Derived Ligands and Their Application for Ruthenium‐Catalyzed Transfer Hydrogenation Reactions in Water: Synthesis of Amines and Alcohols. Issue 12 (5th October 2016) - Sharma, Sushila; Kumar, Manoranjan; Nayal, Onkar S.; Thakur, Maheshwar S.; Bhatt, Vinod; Kumar, Neeraj; Singh, Bikram; Sharma, Upendra
Abstract: Six quinazoline ligands (i.e., 3 –8 ) were synthesized by starting from vasicine and vasicinone, and their applications towards ruthenium‐catalyzed transfer hydrogenation reactions were evaluated. The3 /[RuCl2 ( p ‐cymene)]2 catalytic system was assessed for its use in the ruthenium‐catalyzed transfer hydrogenation reaction of aldehydes, ketones, and imines to give the corresponding alcohols and amines and also assessed for its use in the direct reductive amination of carbonyl compounds with anilines. The3 /[RuCl2 ( p ‐cymene)]2 catalytic system demonstrated good to excellent activity in water with sodium formate as the hydrogen source. Current studies have revealed that among all of the synthesized ligands, those that have secondary amine groups and a rigid backbone are more active towards transfer hydrogenation reactions of unsaturated compounds. Abstract : Natural product derived ligands : Six quinazoline ligands were synthesized by starting from vasicine and vasicinone. The3 /[RuCl2 ( p ‐cymene)]2 catalytic system was assessed for its use in the ruthenium‐catalyzed transfer hydrogenation reaction of aldehydes, ketones, and imines as well as the reductive amination of carbonyl compounds with anilines. Good to excellent catalytic activity was shown in water with sodium formate as the hydrogen source.